2020
DOI: 10.3389/fphar.2020.504624
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Genus Gynura: A Systematic Review

Abstract: Background:Gynura species have been used traditionally to treat various ailments, such as fever, pain, and to control blood glucose level. This systematic review critically discusses studies regarding Gynura species that exhibited antioxidant and anti-inflammatory effects, thus providing perspectives and instructions for future research of the plants as a potential source of new dietary supplements or medicinal agents.Methods: A literature search from internet databases of PubMed, Scopus, Science Direct, e-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 96 publications
(385 reference statements)
0
4
0
Order By: Relevance
“…Gynura species are known to possess anti-inflammatory effects. These anti-inflammatory properties work by modulation of inflammatory cytokine production, inhibition of prostaglandin E 2 and nitric oxide production, cellular inflammatory-related parameters, and inflammation in animal models [ 37 ]. The results of the biological evaluation of GPE have supported the medical usage of this plant as a topical anti-inflammatory agent in Thai traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Gynura species are known to possess anti-inflammatory effects. These anti-inflammatory properties work by modulation of inflammatory cytokine production, inhibition of prostaglandin E 2 and nitric oxide production, cellular inflammatory-related parameters, and inflammation in animal models [ 37 ]. The results of the biological evaluation of GPE have supported the medical usage of this plant as a topical anti-inflammatory agent in Thai traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Gynura procumbens is a plant whose fresh leaves can be consumed raw or cooked 15 . Multiple reports have demonstrated that Gynura procumbens Leaves extract (GLE) contains a variety of secondary metabolites, including quercetin, gallic acid, kaempferol, kaempferol-3-O-β-D-glucopyranoside, kaempferol-3-O-rutinoside, rutin, chlorogenic acid, protocatechuic acid, vanillic acid, syringic acid, caffeic acid, p-coumaric acid, ferulic acid, 3,5-dicafeoylquinate methyl ester, terpenoids, tannins, alkaloids, saponins, and astragali 16,17 . In addition, it possesses a diverse array of pharmacological actions, including antihyperglycemic, antihyperlipidemic, antioxidant, organ-protective, antibacterial, and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has widespread habitats in Africa [ 1 ] and the tropics of Southeast Asia [ 2 ]. G. procumbens possesses a high therapeutic potential and is used as a traditional medicine for rashes, kidney problems, constipation, hypertension, migraines, diabetes, urinary infections, fever, dysentery, cancer, and inflammation [ [3] , [4] , [5] ]. Pharmacological studies have also revealed the potential of G. procumbens as a treatment for anti-hyperlipidemic, anti-herpes simplex virus, anti-cancer, and as an analgesic agent like others medicinal plants [ [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds found in the leaves of G. procumbens have a number of positive health effects [ 12 ]. In this era of rising demand for herbal medicines, the medicinal properties of G. procumbens can be effectively used for the development of novel medications [ 3 , 13 ]. Cuttings, which are the traditional method of propagation for this plant, are unable to meet the plant's large-scale commercial demand, whereas the in vitro culture technique does so quickly, in a sterile environment, and without compromising quality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%